2010
DOI: 10.1089/met.2009.0035
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Syndrome Prevalence, Dietary Intake, and Cardiovascular Risk Profile Among Overweight and Obese Adults 18–50 Years Old From the United Arab Emirates

Abstract: The high prevalence of metabolic syndrome among overweight/obese Emirati adults predisposes this population to increased risk for developing diabetes and cardiovascular disease. Public health involvement targeting poor dietary habits and exercise programs among Emirati citizens is urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 25 publications
3
26
0
Order By: Relevance
“…The prevalence of MS increased from normal weight (8.3%) to overweight (18.8%) to obesity (28.8%) in our study suggesting that these traders were at increased risk of developing CVD. This observation is similar to study among Emirati overweight and obese adults with 40% prevalence of metabolic syndrome [2]. Studies have reported the absence of metabolic abnormalities in some obese individuals with excess body fat [24,25].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The prevalence of MS increased from normal weight (8.3%) to overweight (18.8%) to obesity (28.8%) in our study suggesting that these traders were at increased risk of developing CVD. This observation is similar to study among Emirati overweight and obese adults with 40% prevalence of metabolic syndrome [2]. Studies have reported the absence of metabolic abnormalities in some obese individuals with excess body fat [24,25].…”
Section: Discussionsupporting
confidence: 91%
“…MS predisposes individuals to increased risk for developing DM2 and CVD [2]. The prevalence of MS in traders in our study was 16.3%.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations